Spanish laughter : humor and its sense in modern Spain - Calvo Maturana, Antonio Juan (Studies in Latin American and Spanish history, 2022)
"Why and what have we laughed at in the last two centuries? Is humor merely a means of provoking laughter and entertainment, or of communicating deeper ideas? What are and have been its limits? Spanish Laughter answers these and many other questions through an interdisciplinary study of Spanish humor from the Enlightenment to the present day, analyzing everything from literature and political satire to film and social networks"--